The case for presenteeism - Simen Markussen; Arnstein Mykletun; Knut Røed (Institute for the Study of Labor (IZA), 2010)
Can activation requirements control moral hazard problems in public sickness absence insurance and accelerate recovery? Based on empirical analysis of Norwegian data, we show that it can. Activation requirements not only bring down benefit claims, they also reduce the likelihood that long-term sickness absence leads to inactivity. Our findings show that absentees who are issued graded (partial) absence certificates by their physician have shorter absences and higher subsequent employment rates than they would have had on regular sick leave. We conclude that the activation strategies that in recent years have permeated European and US welfare policy may fruitfully be carried over to sick leave insurance.
Keywords: C26; I18; I38; J48; 330; sick leave; disability; activation; workfare